Long term follow-up of a large patient population with stage 2 and 3 esophageal cancer - Diana M Christensen; Anna K Paulsson; Balkarn S Thind; Trevor T Miller; Jing Zeng; Shilpen A Patel (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Objectives: Patients with stage II and III esophageal cancer are often incurable with surgery alone, suggesting the importance of optimizing other treatments such as chemotherapy and radiation. This retrospective analysis compared the survival and treatment-related toxicities of esophageal cancer patients receiving trimodality therapy to two other common clinical regimens. Methods: Patients with stage II or III esophageal carcinoma who presented for treatment between 1995 and 2016 were eligible for inclusion. Median overall and disease-free survival (DFS) was calculated and compared between those who received Trimodality therapy (T), Surgery alone (S), or Chemoradiation alone (CH + R). Results: This analysis included 358 patients. Median overall survival for T patients was superior (42.8 months, p <0.001) compared to those in the CH + R (21.5 months) and S groups (19.3 months). CH + R patients had the greatest DFS of 21 months, followed by T with 15.5 months, though this difference was not significant (p=0.56). Patient gender (p <0.036) and treatment toxicity (p <0.002) had significant effects on outcome. Median follow-up time for all patients was 22 months (range 1-250 mos). Conclusions: Though five-year overall survival rates for esophageal cancer patients remain close to 20%, neoadjuvant chemoradiation may improve outcomes. This large study with long follow-up demonstrates that patients can be selected for appropriate therapy. Our results suggest that patients receiving trimodality therapy have a higher median overall survival without increased treatment-related toxicity. This data may help guide clinical decision-making and patient selection to improve the survival of patients with advanced esophageal cancer.